2015
DOI: 10.1094/pdis-06-14-0577-re
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glyphosate Application on Sudden Death Syndrome of Glyphosate-Resistant Soybean Under Field Conditions

Abstract: Sudden death syndrome (SDS), caused by Fusarium virguliforme, is an important yield limiting disease of soybean. Glyphosate is used to control weeds in soybean; however, its effect on SDS is not clearly understood. The objective of this study was to examine the impact of glyphosate on SDS, yield, and plant nutrition under field conditions. Fourteen field experiments were conducted in Iowa, Illinois, Indiana, Michigan, Wisconsin, and Ontario, Canada during 2011 to 2013. The experiment consisted of six treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…We found no effects of any of the variables studied on yield. This is in line with previous studies which found no negative effect of glyphosate or the GR transgene on yield of GR soybean . The most extensive set of studies on the effects of glyphosate on yield of GR soybean was published in 1995, the year before this GR crop was first grown commercially by farmers .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found no effects of any of the variables studied on yield. This is in line with previous studies which found no negative effect of glyphosate or the GR transgene on yield of GR soybean . The most extensive set of studies on the effects of glyphosate on yield of GR soybean was published in 1995, the year before this GR crop was first grown commercially by farmers .…”
Section: Discussionsupporting
confidence: 89%
“…This study evaluated the effects at 17–23 locations over 3 years and found no effect on yield. Kandel et al . reported at some locations glyphosate‐treated GR soybean had significantly greater yields than GR soybean in which herbicides other than glyphosate were used for weed management.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Similar results were reported by Njiti et al 52 A recent multi-year study conducted across several US states and one Canadian province provided further evidence that neither the glyphosate resistance trait nor application of glyphosate to these soybean lines had any impact on the severity of sudden death syndrome. 53…”
Section: Glyphosate Resistant Soybean-fusarium Virguliforme Interactionmentioning
confidence: 99%